Chitosan: A Naturally Occurring Viable Alternative to Nystatin as an Antifungal Agent Incorporated in Heat-Polymerized Denture Base Resin II - Trunaya Bhatlekar; Siddharth Swarup; Rajashri Patil; Sahjid Mukhida; Akansha Bhandari; Amit Jagtap; Nageswari Gandham (Scientific Dental Journal, 2023)
Background: Out of its various derivatives, low molecular weight (LMW) chitosan is known to have improved solubility and antifungal properties. Nystatin the standard antifungal drug discontinued from therapy due to resistant Candida strains emerged. Objectives: This study aims to compare the previously obtained results of the antifungal capacity of low molecular weight chitosan and nystatin against Candida albicans biofilm on Triplex heat-cure denture bases after 7 and 14 days with their antifungal efficacy on Trevalon-High Impact (HI) heat-cure denture bases. Methods: A Trevalon heat-cure with HI, utilizing the typical compression molding process, was employed to create 10 specimens from Polymethyl Methacrylate (PMMA) acrylic resin. All specimens were pre-treated with imitation saliva for 72hours to development of biofilm. Two groups of five specimens each were established. On the fourth day after biofilm formation, Group A was immersed in LMW chitosan solution, whereas Group B was immersed in a nystatin solution. On the 11th day, the specimens were treated again using antifungal suspension, as per the assigned groups, and the complete maturation of the residual biofilm was allowed to occur until the 14th day. Results: The results in Nystatin group demonstrated a substantial reduction of 5 times or more in the Colony Forming Units (CFU) of Candida colonies in the biofilm from the 7th to the 14th day. On the other hand, in Chitosan group, the CFU of Candida colonies showed an insignificant decrease. When comparing CFU between both groups at one week, a nonsignificant reduction while a significantly lower CFU count was noted at 14th day in the chitosan group compared to the nystatin group, with a significant p-value of 0.002. Conclusion: The current study results suggest the potential for expanding the use of chitosan in denture-wearing patients in the future, contributing to the maintenance of optimal dental and overall health.